Pengaruh Customer Relationship Management (CRM) Terhadap Keputusan Pembelian - Onassis, Sherla; Utama, Tasik; Sutarno (Journal of Trends Economics and Accounting Research, 2024)
PT. Gunung Sawit Mas (GSM) is a limited liability company engaged in manufacturing Palm Oil (CPO). CPO is an abbreviation of Crude Palm Oil. The purpose of this research is to determine the influence of Customer Relationship Management (CRM) on purchasing decisions at PT. Mount Sawit Mas. The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The research population that will be used in this research is all consumers who make purchases from companies totaling 137 consumers (similar palm oil companies). Because the population used is 137 consumers, the population will be reduced using the Slovin sampling technique with a confidence level of 95% and an error rate of 5%, where 102 samples are obtained. The analysis technique used is simple linear analysis and statistical tests, namely t-test (partial) using SPSS (statistical package for the social sciences) software. The test results show that Customer Relationship Management has a positive and significant effect on consumer purchasing decisions at PT. Mount Sawit Mas.